Making Sense of Place: An Ethnography of Toxicant Encounters in South Portland, Maine - Perkins, Lucy. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Kristin Skrabut, and Penn Loh.; Keyword: Urban planning.